Efektivitas promosi melalui media sosial instagram terhadap minat berkunjung wisatawan di Agrowisata Kebun Teh Pagilaran Batang - Maulana, Rizky; Dewi, Shinta Fatma; Syaifulloh, Muhammad (Journal of Management and Digital Business, 2024)
The growth of social media in Indonesia is an opportunity to maximize its potential as a medium for communication and sharing information, one of which is by utilizing Instagram social media as a platform for promotion and creating exciting content to attract tourists. This study aims to determine the influence of Instagram social media on tourists' interest in visiting the Pagilaran Batang Tea Garden Agrotourism. This study uses simple regression with 100 respondents as observations. The research analysis results show that Instagram social media influences tourists' interest in visiting because visitors are familiar with hashtags, geotags, shares, comments, and image or video-sharing features. In this case, Instagram social media is one of the factors that significantly influences tourists' interest in visiting. This finding confirms that Instagram as a "promotional media" is effective for promoting any tourist attraction, even though the location and type of tourist attraction are different.